Adequacy of high-risk prenatal care at a referral hospital - Costa, Lediana Dalla; Perondi, Alessandro Rodrigues; Cavelheiri, Jolana Cristina; Ferreira, Andressa de Souza; Teixeira, Gessica Tuani; Bortoloti, Durcelina Schiavoni (Rev Rene, 2016)
Objective: to describe the adequacy of prenatal care for high-risk pregnancy in a referral hospital. Methods: descriptive, retrospective and documentary study. The sample was 73 pregnant women who had a childbirth, during the collection period. The Kessner index was used to assess the quality of care, validated instrument in Brazil. For analysis of the information, descriptive statistics and distribution of relative frequencies were used. Results: among the 73 pregnant women, 47.9% were young adults, 50.7% were married, and 52.0% had only primary level. According to the Kessner Index, the intermediate adjustment prevailed. Conclusion: the main finding of this study was the intermediate adequacy of prenatal high risk. It was also found that pregnant women initiated prenatal care late in high risk, leading to reduced number of consultations, clinical procedures, obstetric and laboratory tests.